2012
DOI: 10.1016/j.anorl.2011.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of tumour multifocality in thyroid papillary microcarcinoma based on a series of 160 cases

Abstract: Tumour multifocality does not appear to have a prognostic impact in PTMC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 9 publications
2
15
0
4
Order By: Relevance
“…Similar to our results (although with different inclusion criteria), others found no association between multifocality and tumour recurrence [39,40]. Thus, the prognosis of multifocal nature of the disease remains controversial, although the recently developed ATA guidelines [6] have associated a higher risk of tumour recurrence of 4-6% with multifocal disease regardless of the tumour size.…”
Section: Discussionsupporting
confidence: 80%
“…Similar to our results (although with different inclusion criteria), others found no association between multifocality and tumour recurrence [39,40]. Thus, the prognosis of multifocal nature of the disease remains controversial, although the recently developed ATA guidelines [6] have associated a higher risk of tumour recurrence of 4-6% with multifocal disease regardless of the tumour size.…”
Section: Discussionsupporting
confidence: 80%
“…Extrathyroidal extension was another predictor for recurrence, consistent with previous studies [17][18][19]. However, some studies of the prognostic impact of tumor multifocality in papillary thyroid microcarcinoma (PTMC) have suggested that multifocal lesions do not appear to have prognostic impact in PTMC [20]. Given the high incidence of multifocality in PTMC, 20-40% [21][22][23], further studies of small PTC tumors are needed to investigate the true role and influence of multifocality in this subtype of PTC.…”
Section: Discussionsupporting
confidence: 63%
“…However, some studies on the prognostic impact of tumour multifocality in PTC especially microcarcinomas have suggested that multifocal lesions do not appear to have prognostic impact [35]. Our study has shown that the size of concurrent tumours is important on whether multifocality represents greater tumour burden and better predictor of more aggressive behaviour of papillary thyroid cancer.…”
Section: Discussionmentioning
confidence: 69%